The Relationship Between Sleep Health, Sleep Regularity, Optimism, and Well-Being With Self-Rated Health: A Study on Healthcare Professionals - Sohrab Amiri; Duston Boyd; Oumara Alajlouni; Sana Osama Al-Rawi; Amal Samra; Alexander Kieu; Moien A.B. Khan (Sleep Medicine Research)
Background and Objective This study investigates the impact of sleep, well-being, and optimism on self-rated health among healthcare professionals in the United Arab Emirates (UAE). Methods A cross-sectional approach was employed, using Pearson correlation and linear regression to analyze the relationship between sleep, well-being, optimism, and self-rated health among health care professioansl in the UAE. Results The age range of the participants was between 20–65 years, and they were predominantly female (68.7%). Significant predictors of self-rated health included well-being (p < 0.001), optimism (p = 0.004), and sleep circadian regularity (p = 0.009), explaining 10% of the variance in self-rated health (R2 = 0.103). Among the participants, 84.1% worked in public hospitals, and 15.9% in private hospitals. Regarding body mass index, 43.9% were of normal weight, 4.8% underweight, 32.4% overweight, and 18.9% obese. Males reported higher well-being and sleep continuity scores than females. Conclusions The study highlights the critical role of sleep health, well-being, and optimism in shaping healthcare professionals’ self-rated health. These results suggest that improving these mental health factors can positively influence healthcare professionals’ self-rated health, potentially enhancing their performance and patient care quality. Further research is needed to identify additional determinants and to establish causal relationships through longitudinal studies.